The fabrication of wood alternative material from cassava rhizome and cassava peel pulp - Minaboon, Nichapha; Khamput, Prachoom; Watcharasawe, Kongpop; Malai, Attapole (Journal of Applied Research on Science and Technology (JARST), 2024)
The increasing demand for wood alternative material in construction and furniture. Corresponds to global efforts to reduce pressure on forests, necessitating the exploration of alternative materials to wood. The agricultural industry can not only supply raw materials from non-wood plants but also waste material and byproducts. The aim of this research was to explore and manufacture wood alternatives using cassava rhizomes and cassava peels, thereby valorizing agricultural waste. The research methodology involved blending milled rhizomes and cassava peels with urea-formaldehyde resin followed by a hot-pressing process to form the final product. The samples size for this study was 450x450x10 mm were made using 6-10 percent urea-formaldehyde resin by weight of the composite materials aiming to achieve a sheet density about 600 kg/cu-m. Three distinct ratios of Cassava rhizome to cassava peel pulp were examined as potential wood substitutes. All test results of sample were compared with the industrial standards outlined in Thai Industrial Standard. The study found that wood substitutes created from Cassava rhizome and Cassava peel pulp combined with urea-formaldehyde resin could meet the set standards. Cassava rhizome improves important properties like density, moisture content, thickness swelling, formaldehyde content, modulus of rupture, and modulus of elasticity according to TIS 876-2547 standards. However, adding peel pulp tends to reduce these qualities. There is no significant change in the density of the wood-alternative materials. However, a 10% urea formaldehyde content improves the mechanical properties. The study found that wood substitutes created from Cassava rhizome and Cassava peel pulp combined with urea-formaldehyde resin could meet the set standards. Moreover, the production cost of these wood substitute materials was lower than the prevailing market prices. This study disseminates knowledge from research that utilizes cassava rhizomes and peels to create sheet like wood substitute materials. Using modern methods and appropriate technologies, cassava rhizomes and peels can be transformed into a diverse range of wood substitute products, and capable of effectively competing with wood and other materials in the future.